Corpo e adoecimento na percepção docente - Schuster, Marcieli (2016)
This research addresses the issue of body perception and illness by teachers’ perspective. The research, at first, aimed to identify what are the diseases that most affect teachers and their consequent absence from work performed in the Municipal Education Network of Cascavel, PR, Brazil. Secondly, from the data collected in the medical certificates, we reflected on these illnesses through interviews with teachers, in order to apprehend if, in the perception of such professionals, the diseases could be related to their work routines and what are their body and illness perceptions. To achieve these goals, surveys were conducted for a quantitative and qualitative analysis, by Laurence Bardin content analysis technique (2011), in medical certificates registered in 2014 by the Health and Safety Division of work of the municipal city hall of Cascavel. We also conducted semi-structured interviews with the teachers, in order to meet the educators' relationship with their selves, from their understanding about body-being-subject in their profession. We problematized the body perception of the surveyed teachers and the relationships they established between the teaching work and the illness, from the perspective of the theoretical field of comprehensive sociology of Michel Maffesoli and the illness in the teaching profession from the perspective of Codo and Cruz. The analysis of the registered medical certificates evidence, as partial results, that from the 394 investigated certificates were 96% of female teachers, the average age was 41.83 years old and the most frequent diseases were Mental or Emotional Disorders (25.38%), Traumas and Bruises (22.84%) and Muscle Disorders Skeletal (13.95%). In the analysis of the interviews we pointed out that the professional devaluation has been a major cause of illness reasons and consequently for removals of the teachers of Cascavel Education Municipal Network, besides the bad working conditions from a lack of adequate physical structure, too many students/room, surplus labor routine, among others